Copper(II) ion-exchanged montmorillonite as catalyst for the direct addition of N-H bond to CC triple bond - Joseph, Trissa; Shanbhag, G. V.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
An efficient synthesis of phenyl-(1-phenylethylidene)amine using copper-exchanged montmorillonite clay (Cu K-10) is demonstrated. The catalyst was characterized using UV-vis, XRD, BET surface area measurements, pyridine adsorption etc. The XRD and surface area measurement show that the structural characteristics of the support montmorillonite K-10 (K-10) are preserved after Cu exchange. The hydroamination of phenyl acetylene with aniline was carried out in toluene under reflux condition in N-2 atmosphere at 393 K. The reaction is highly regio-selective for only Markovnikoff's addition of an-tine to CC multiple bond and proceeded smoothly to completion. The reaction conditions were optimized to obtain complete conversion with respect to phenyl acetylene. Reaction data showed that the activity of the catalyst in hydroamination reaction is greater at higher reaction temperatures and nonpolar solvents and NZ pressure promotes the reaction drastically. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyne; Aniline; Catalyst; hydroamination; K-10 montmorillonite clay; phenyl acetylene